Magnetic Resonance Imaging–Derived Renal Oxygenation and Perfusion During Continuous, Steady‐State Angiotensin‐II Infusion in Healthy Humans. Issue 3 (March 2016) - van der Bel, René; Coolen, Bram F.; Nederveen, Aart J.; Potters, Wouter V.; Verberne, Hein J.; Vogt, Liffert; Stroes, Erik S. G.; Krediet, C. T. Paul
Abstract : Background: The role of kidney hypoxia is considered pivotal in the progression of chronic kidney disease. A widely used method to assess kidney oxygenation is blood oxygen level dependent (BOLD)–magnetic resonance imaging (MRI), but its interpretation remains problematic. The BOLD‐MRI signal is the result of kidney oxygen consumption (a proxy of glomerular filtration) and supply (ie, glomerular perfusion). Therefore, we hypothesized that with pharmacological modulation of kidney blood flow, renal oxygenation, as assessed by BOLD‐MRI, correlates to filtration fraction (ie, glomerular filtration rate/effective renal plasma flow) in healthy humans. Methods and Results: Eight healthy volunteers were subjected to continuous angiotensin‐II infusion at 0.3, 0.9, and 3.0 ng/kg per minute. At each dose, renal oxygenation and blood flow were assessed using BOLD and phase‐contrast MRI. Subsequently, "gold standard" glomerular filtration rate/effective renal plasma flow measurements were performed under the same conditions. Renal plasma flow decreased dose dependently from 660±146 to 467±103 mL/min per 1.73 m 2 (F[3, 21]=33.3, P <0.001). Glomerular filtration rate decreased from 121±23 to 110±18 mL/min per 1.73 m 2 (F[1.8, 2.4]=6.4, P =0.013). Cortical transverse relaxation rate (R2*; increases in R2* represent decreases in oxygenation) increased by 7.2±3.8% (F[3, 21]=7.37, P =0.001); medullar R2* did not change. Cortical R2* related to filtration fraction ( R 2 0.46, P <0.001). Conclusions: By direct comparison between "gold standard" kidney function measurements and BOLD MRI, we showed that cortical oxygenation measured by BOLD MRI relates poorly to glomerular filtration rate but is associated with filtration fraction. For future studies, there may be a need to include renal plasma flow measurements when employing renal BOLD‐MRI.